2021
DOI: 10.1016/j.envpol.2020.115901
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for wintertime deposition of anthropogenic light-absorbing particles on the Central Andes cryosphere

Abstract: Ice and snow in the Central Andes contain significant amounts of light-absorbing particles such as black carbon. The consequent accelerated melting of the cryosphere is not only a threat from a climate perspective but also for water resources and snow-dependent species and activities, worsened by the mega-drought affecting the region since the last decade. Given its proximity to the Andes, emissions from the Metropolitan Area of Santiago, Chile, are believed to be among the main contributors to deposition on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…We find that for the village 34% (1 µg m −3 ) of PM 2.5 , on average, is transported from the metropolitan area. This is consistent with the mountain-valley circulation patterns aforementioned, leading to the intrusion of urban air masses deep into the canyon (Lapere et al, 2021). We acknowledge that the estimate of 34% is probably larger than reality since the HTAP inventory does not capture properly local emissions in the village of San Gabriel, which likely dominate the signal, especially with wood burning for residential heating being largely used in such villages in wintertime.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We find that for the village 34% (1 µg m −3 ) of PM 2.5 , on average, is transported from the metropolitan area. This is consistent with the mountain-valley circulation patterns aforementioned, leading to the intrusion of urban air masses deep into the canyon (Lapere et al, 2021). We acknowledge that the estimate of 34% is probably larger than reality since the HTAP inventory does not capture properly local emissions in the village of San Gabriel, which likely dominate the signal, especially with wood burning for residential heating being largely used in such villages in wintertime.…”
Section: Resultssupporting
confidence: 79%
“…As a result, the PM 2.5 emitted in large amounts mostly remain trapped within this shallow mixing layer. Injection of polluted air masses into the lower FT can also occur, through mountain venting, as described in Lapere et al (2021), explaining why residual concentrations of 1 to 5 µg m −3 are observed higher up in the baseline and contribution scenarios at the latitude of Santiago (Fig. 9b and 9c).…”
Section: Advection Processesmentioning
confidence: 86%
“…Again, mountain-valley circulation accounts for this observation; afternoon westerlies blow O 3 precursors, present in large amounts in urban air masses, towards the Andes. The NO x lifetime is a few hours at most, depending on the reactivity of VOCs and NO 2 density (e.g., Laughner and Cohen, 2019), while most VOCs have an atmospheric lifetime of several days (e.g., Monod et al, 2001) so that, on the way, NO x are consumed more than VOCs. Consequently, while urban air is mostly a NO x -rich environment, precursors ratios become more balanced, along with the export, to create more favorable conditions for O 3 formation on reaching less urbanized areas.…”
Section: Summertime Omentioning
confidence: 99%
“…3.2.2). But NO x have a lifetime that is much shorter than most VOCs (e.g., Monod et al, 2001;Laughner and Cohen, 2019), and when the polluted air parcels are lifted up, the ratio becomes more balanced as NO x is consumed closer to the ground. Due to these asymmetric lifetimes and, hence, export, at some point on the vertical profile the ratio becomes favorable (Fig.…”
Section: Advection Processesmentioning
confidence: 99%
“…It simulates the physical–chemical processes of the different atmospheric pollutants based on emissions from the main anthropogenic sectors: residential, transportation, industry, and energy. This modeling system has been successfully applied to simulate the dispersion of atmospheric pollutants in central and southern Chile as well as the exposure to particulate matter of public transport users [ 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%